2015
DOI: 10.1039/c5nr05164a
|View full text |Cite
|
Sign up to set email alerts
|

2D nanosheet molybdenum disulphide (MoS2) modified electrodes explored towards the hydrogen evolution reaction

Abstract: We explore the use of two-dimensional (2D) MoS2 nanosheets as an electrocatalyst for the Hydrogen Evolution Reaction (HER). Using four commonly employed commercially available carbon based electrode support materials, namely edge plane pyrolytic graphite (EPPG), glassy carbon (GC), boron-doped diamond (BDD) and screen-printed graphite electrodes (SPE), we critically evaluate the reported electrocatalytic performance of unmodified and MoS2 modified electrodes towards the HER. Surprisingly, current literature fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 83 publications
(267 reference statements)
3
72
0
Order By: Relevance
“…This places the electrodes in the following order of reactivity: SPE > EPPGE > GCE > BDDE > BPPGE. It is noted that the value for the SPEs are consistent with those in previous literature [44][45][46]. As the peak-to-peak separations for these carbon based electrodes are similar when utilizing hexammineruthenium(III) chloride, ( Table 2) further benchmarking was undertaken using the Fe 2+ /Fe 3+ redox couple, since this is an inner-sphere probe that is known to be extremely sensitive to surface orientated functional groups, especially carbonyl groups.…”
Section: Resultssupporting
confidence: 70%
“…This places the electrodes in the following order of reactivity: SPE > EPPGE > GCE > BDDE > BPPGE. It is noted that the value for the SPEs are consistent with those in previous literature [44][45][46]. As the peak-to-peak separations for these carbon based electrodes are similar when utilizing hexammineruthenium(III) chloride, ( Table 2) further benchmarking was undertaken using the Fe 2+ /Fe 3+ redox couple, since this is an inner-sphere probe that is known to be extremely sensitive to surface orientated functional groups, especially carbonyl groups.…”
Section: Resultssupporting
confidence: 70%
“…With the ever-increasing ecological demand for the utilisation of renewable energy sources, such as solar and wind, the development of sustainable energy conversion and storage technologies are paramount [1][2][3]. One of the most successful (in terms of commercialisation) effective energy storage devices has been the lithium-ion battery (LIB).…”
Section: Introductionmentioning
confidence: 99%
“…However, the requirement of expensive platinum (Pt) as an catalytic electrode material in both electrolysers and fuel cells has severely limited the cost competitiveness of a hydrogen based energy economy. 3 In order to lower the production costs associated with H 2 (gas), research has recently focused on nding a cheaper more earth abundant electrode material to catalyse the Hydrogen Evolution Reaction (HER) (2H + + 2e À / H 2 ), 4 which is the focus of commercially available electrolysers. Studies such as Ji et al 5 have shown that 2D-MoS 2 can be used as an effective electrocatalyst towards the HER.…”
Section: Introductionmentioning
confidence: 99%
“…2(A). 3 For details on how the Tafel slopes displayed in Fig. 2(B) )) is subsequently followed by a decrease in current density and/or plateauing effect.…”
mentioning
confidence: 99%